2006
DOI: 10.1590/s1516-35982006000600031
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento ingestivo de ovinos alimentados com dietas compostas de silagem de capim-elefante amonizada ou não e subprodutos agroindustriais

Abstract: RESUMO -Foram estudados os efeitos do uso de silagem de capim-elefante amonizada ou não com uréia (5% na base da MS) e da substituição do concentrado (milho e farelo de soja) por farelo de cacau (FC) ou torta de dendê (TD) na dieta sobre o comportamento ingestivo de ovinos Santa Inês. Dezoito ovinos machos não-castrados (peso médio inicial de 22,62 kg), alojados em baias individuais, foram distribuídos em delineamento experimental inteiramente casualizado, com seis tratamentos, dois volumosos (silagem de capim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
4
14

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 13 publications
(7 reference statements)
2
13
4
14
Order By: Relevance
“…It has been observed that the use of several additives in sugarcane has brought great benefits such as increase of the nitrogenous fraction (Pires et al, 2004b;Carvalho et al, 2006a;Amaral, 2007). However, the use of alkaline additives such as sodium hydroxide and calcium oxide does not contribute to the increase of nitrogen uptake, sometimes triggering a greater effect of hydrolysis on the cell wall of roughages, improving the fiber digestibility and intake (Andrade et al,R.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that the use of several additives in sugarcane has brought great benefits such as increase of the nitrogenous fraction (Pires et al, 2004b;Carvalho et al, 2006a;Amaral, 2007). However, the use of alkaline additives such as sodium hydroxide and calcium oxide does not contribute to the increase of nitrogen uptake, sometimes triggering a greater effect of hydrolysis on the cell wall of roughages, improving the fiber digestibility and intake (Andrade et al,R.…”
Section: Introductionmentioning
confidence: 99%
“…Consumos (kg/dia) de matéria seca (CMS) e de fibra em detergente neutro (CFDN), tempo (min) despendido em alimentação, ruminação e ócio, número de bolos ruminados por dia e o tempo gasto por bolo (segundos) em cordeiros alimentados com dietas contendo diferentes níveis de feno de amoreira Carvalho et al (2006), que, ao estudarem a inclusão de farelo de cacau ou torta de dendê em substituição ao concentrado, nas dietas de ovinos da raça Santa Inês em confinamento, não observaram alterações no número de bolos ruminados (n o /dia) e no tempo de mastigações/bolo (seg); e por Carvalho et al (2004), ao analisarem a inclusão de farelo de cacau ou torta de dendê no concentrado, na dieta de cabras leiteiras.…”
Section: Resultsunclassified
“…The recent progress in nutrition, reproduction, and genetic improvement has also exerted a positive influence on meat and milk production. However, a better understanding of animal behavior is needed in order to better manage food consumption, which would allow farmers to adjust the feeding of animals to improve their performance (CARVALHO et al, 2006;PIRES et al, 2009). To reduce the cost of feeding and to increase profitability, it is necessary to use alternative feeds that improve animal productivity, while also maintaining a high quality of meat and milk (OLIVEIRA et al, 2010) and meeting the nutritional needs of the animals.…”
Section: Introductionmentioning
confidence: 99%
“…However, the cakes and meals produced by the biodiesel industry, for example, have a high potential for use in the feeding of ruminants, considering their elevated protein and ethereal extract concentrations, which characterize them as high-protein, highenergy foods that can meet the nutritional needs of animals . Another byproduct, palm kernel meal (PKM), is obtained during the extraction of palm oil from Elaeis guineensis, through the use of pressure and organic solvents, and although the meal contains a high fraction of cell wall material (CARVALHO et al, 2006), PKM is still considered a high-energy and average-quality food for ruminants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation